Glassy poly(methacrylate) terpolymers with covalently attached emitters and sensitizers for low‐power light upconversion. Issue 14 (8th April 2015) - Lee, Soo Hyon; Thévenaz, David C.; Weder, Christoph; Simon, Yoan C.
ABSTRACT Low‐power light upconversion by triplet–triplet annihilation (TTA‐UC) was only recently demonstrated in glassy polymers and the upconversion efficiency in these materials is typically much lower than in solution. As aggregation of the chromophores was thought to be the culprit, we here report the covalent tethering of a suitable chromophore pair to a polymeric backbone. The new materials were based on the sensitizer‐bearing monomer palladium meso‐phenoxy‐tris(heptyl)porphyrin‐ethylmethacrylate (PdmPH3PMA), which was copolymerized with a diphenylanthrancene methacrylate (DPAMA), as the emitter‐bearing monomer, and methyl methacrylate (MMA) as an optically inert comonomer. The DPA content was kept within a narrow range of 30–37 wt %, while the PdmPH3PMA content was varied between 0.73 and 0.012 wt %. To explore additional compositions, blends of a high‐porphyrin‐content terpolymer with a DPAMA‐MMA copolymer were also prepared. All of the materials studied were processed into thin films by solution‐casting and displayed blue TTA‐UC emission. The UC emission intensity was found to strongly depend on the composition and the underlying effects were investigated through a systematic study. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 1629–1639